Treatment of sleep disturbance following stroke and traumatic brain injury: a systematic review of conservative interventions. Issue 13 (19th June 2022) - Lowe, Alex; Bailey, Mark; O'Shaughnessy, Terry; Macavei, Vladimir
Abstract: Purpose: Sleep disorders are common following stroke and traumatic brain injury. We present a systematic review of the literature investigating conservative interventions to improve sleep in these populations. Materials and methods: The PRISMA statement was used. Embase, PubMed, and the Cochrane library were searched for all experimental studies published prior to 28th March 2020 that assessed conservative interventions to improve the sleep or sleep disorders of adults with a history of stroke or traumatic brain injury (TBI). Two authors reviewed publications of interest and risk of bias assessments were performed using the Cochrane Risk of Bias Tool or the Methodological Index for Non-Randomised Studies instrument. Results: Twenty-three publications were included in this systematic review. Meta-analyses were not performed due to study heterogeneity. Psychotherapy-based approaches might be useful for sleep disturbance after TBI and acupuncture may help improve insomnia or sleep disturbance following stroke or TBI, respectively. The evidence was less clear for morning bright light therapy and exercise. Limitations included a single author performing primary searches, only English publications, the reporting of secondary outcome measures, and sleep disorder diagnoses. Conclusions: Some conservative interventions might be useful for improving sleep disturbance or disorders in these populations, but further research is required. IMPLICATIONS FOR REHABILITATION: Sleep disturbance is common following stroke and traumatic brain injury, with insomnia and obstructive sleep apnoea being the most frequently diagnosed sleep disorders. Psychotherapy-based approaches might be useful for sleep disturbance after TBI and acupuncture may help improve insomnia or sleep disturbance following stroke or TBI, respectively. Morning bright light therapy appeared to be more beneficial for fatigue rather than sleep disturbance after TBI, and the evidence for exercise was less clear.